Experimental study on the biaxial bending cyclic behaviour of RC columns - Rodrigues, H. (2010)
The available experimental studies on the inelastic 3D response of axially loaded members under biaxial bending moment loading histories are limited. Possibly, this is partially due to the uncertainty of combining bending moment’s histories in the two orthogonal directions that adds considerable complication to the problem. Three types of cantilever reinforced concrete columns with constant axial load were subjected to cyclic uniaxial and biaxial tests. It was intended to gain enhanced knowledge concerning the behaviour or RC columns that allows for the calibration of simplified non-linear models. The experimental campaign is described, test results are presented and discussed comparing the uniaxial and the biaxial tests and the effect of the different biaxial load paths in the columns behaviour.